TEACHING MATERIALS AND TECHNIQUES NEEDED BY FOREIGN STUDENTS IN LEARNING BAHASA INDONESIA - Imam Suyitno; Gatut Susanto; Musthofa Kamal; Ary Fawzi (Jurusan Sastra Indonesia, 2017)
The study outlined in this article aimed to describe teaching materials and techniques needed by foreign students in learning Bahasa Indonesia. In learning BIPA, teaching materials and learningtechniques are important aspects that need to be selected and organized seriously. The characteristics and objectives of BIPA learners are the main factors that need to be considered and understood by BIPA teachers. In this case, BIPA teachers must master the pedagogical norm of BIPA learning. Understanding of pedagogical norms will lead BIPA teachers to be able to determine the materials and learning techniques in accordance with the conditions of BIPAstudents.